Fire loads calculation in the school library: A case study - Nurul Izzah, Ab Razak; Nurud Suria, Suhaimi; Wan Zaiton, Wan Sulaiman (Penerbit Universiti Malaysia Pahang, 2024)
A combustible material is one of fire hazard where the numberof combustible materials or fire load could affect the heat release and fire severity in enclosure. A library is a facility where books and information sources are kept. People can reach them more easily for a variety of reasons such as knowledge. As the library is full of combustible materials such as books, the probability of fires happening there is high. The awareness of the danger of fire caused by fire load is low because most people think that the occurrence of fire in the school library is low. Therefore, this research objectives aim to identify the types of fire loads that are present in the library and to determine what type of fire load has the highest contribution to fire hazard. The determinations of fire load were conducted by using combination of fire load survey method, weighing and inventory method. In this study, the paper is higher than other combustible material that is 27705.6 MJ and the total of fire load density of the library is 234211.9 MJ/m2 that is fall under high class of fire. Result from fire load survey can help to determine the sufficient requirements of fire suppression in school library as well as fire fighters’ intervention strategy. Furthermore, this study contributes to fire risk assessment towards life safety, property, and environmental damage thus improving the fire safety measures and preparedness in educational settings.